Karakteristik Yoghurt Kacang Hijau dengan Penambahan Ekstrak Daun Kelor (Moringa oliefera) - Intan Kusumaningrum; Sri Rejeki Retna Pertiwi; Deti Nirmala (Universitas Djuanda, 2018)
ABSTRACTYoghurt can be made from leguminose. In this research yogurt made from mungbean with addingl extract kelor leaves. This research is aim to know characteristic of mungbean yoghurt with adding extracts kelor leaves. This research used Completely Randomized Design (CDR) factorial. First factor is starter consentratiton with three treatment level 5%, 10%, and 15%. The second factor is extracts kelor leaves consentration with two treatment 5% and 10%. Analysis was about total lactic acid, pH value, amount of Lactic Acid Bacteria, and viscosity. The best yoghurt will be analysis characteristic of sensory ( quality of sensory and hedonic), proksimat (ash, protein, and fat content) and calcium. The best yoghurt is yoghurt with starter 5% and extract kelor leaves 5% contains 1,03% total lactic acid, pH value 4,54, total lactic acid bacteria 1,5 × 108cfu/g, viscocity 2200 cP, ash content 1,25%, protein content 5,58%, fat content 0,94%, and calcium 52,28 mg/100g.